2023
DOI: 10.1002/advs.202302318
|View full text |Cite
|
Sign up to set email alerts
|

TRIM21‐Promoted FSP1 Plasma Membrane Translocation Confers Ferroptosis Resistance in Human Cancers

Jun Gong,
Yuhui Liu,
Wenjia Wang
et al.

Abstract: Ferroptosis, an iron‐dependent form of regulated cell death driven by excessive accumulation of lipid peroxides, has become a promising strategy in cancer treatment. Cancer cells exploit antioxidant proteins, including Ferroptosis Suppressor Protein 1 (FSP1), to prevent ferroptosis. In this study, it is found that the E3 ubiquitin ligase TRIM21 bound to FSP1 and mediated its ubiquitination on K322 and K366 residues via K63 linkage, which is essential for its membrane translocation and ferroptosis suppression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…There was one previous study with ndings similar to ours showing that the E3 ubiquitin ligase TRIM21 binds to FSP1 and facilitates its ubiquitination, which is crucial for the membrane translocation of FSP1 and its ability to suppress ferroptosis in multiple gastrointestinal (GI) tumors 13 . This means that ubiquitination of FSP1 proteins is a critical requirement for their function.…”
Section: Discussionsupporting
confidence: 67%
“…There was one previous study with ndings similar to ours showing that the E3 ubiquitin ligase TRIM21 binds to FSP1 and facilitates its ubiquitination, which is crucial for the membrane translocation of FSP1 and its ability to suppress ferroptosis in multiple gastrointestinal (GI) tumors 13 . This means that ubiquitination of FSP1 proteins is a critical requirement for their function.…”
Section: Discussionsupporting
confidence: 67%
“…4J ). To determine the specific binding sequence, a series of TNKS1BP1, TRIM21, and CNOT4 truncation mutants were constructed according to previous studies [ 23 , 30 , 31 ] for co-IP analysis (Fig. 4K ).…”
Section: Resultsmentioning
confidence: 99%
“…33,41 Yuan et al 42 identified YTH N6-methyladenosine RNA binding protein C1 (YTHDC1) as a tumor progressive suppressor through the modulation of FSP1 mRNA stability. Additionally, Gong et al 43 found that tripartite motif containing 21 (TRIM21) binds to FSP1 and mediates its ubiquitination on K322 and K366 residues through K63 linkage in gastrointestinal tumors, leading to tumor progression. However, despite the critical role of FSP1, limited FSP1 inhibitors have been identified so far, with iFSP1 being the most popular one.…”
Section: Discussionmentioning
confidence: 99%